Practice of the second conviction for counter-revolutionary crimes in activity of organs of state security of the USSR on the Donetsk area - Olena Luhova (Cхід, 2013)
The article is devoted the category of citizens, which twice tested repressions in post-war time for a the same crime. On the basis of study of statistical materials of card index of the rehabilitated persons atDonetskstate administration, and also documents of a particular branch record office of security of Ukraine Service an author draws conclusion about the scales of repressions in relation to this group of population. Legal bases of repressive actions of the state are analysed in the article, and also drawn conclusion about reasons of appearance in activity of organs state securities of theUSSRof practice of the second conviction are for counter-revolutionary crimes.